Design concepts for cryogenic cooling systems for all-electric thrust aircraft propulsion systems. - Palmer, Joseph (Cranfield University, 2016)
The aim of this thesis is to investigate concepts and possibilities for cryogenic cooling systems within future superconducting all-electric thrust aircraft (AETA) electrical networks. The research comprises of a combination of qualitative and quantitative analysis, following the systems engineering process where possible. The thesis presents a modified version of the Rolls-Royce systems engineering process suitable for early stage conceptual design that was used to enable decision-making analysis of conceptual cryogenic systems. The research has led to a robust choice of cryocooler, a toolset capable of design space analysis, and determination of where future research efforts should be concentrated for eventual successful implementation. The thesis begins by gathering information from literature about the various topics of expertise in this project, and then taking a systems engineering approach to design using the Rolls-Royce process as a guide. The most likely concept for cryocooling was identified through qualitative analysis as the reverse-Brayton cycle through function means analysis. A set of numerical models for superconducting machines and cables were developed to examine the interrelationships that exist within a basic superconducting electrical network. Two cryocooler models were generated; a single-stage and a two-stage reverse-Brayton cryocooler. It was found that the single stage option could only be used for the MgB₂ liquid hydrogen-cooled concept. The two-stage design was deemed feasible for the MgB₂ liquid methane-cooled concept and for the BSCCO liquid methane and air cooled concepts. Furthermore, it was found that after overall temperature configuration, the compressor and turbine polytropic efficiencies were the most critical technologies to develop. The key contributions to knowledge include a set of design assessment tools that can rapidly assess the feasibility of high-level cryocooler concepts. The development of the world’s first fully superconducting and cryogenic support system models that can be used to determine future research direction are also a key contributions. The key industrial benefit to the sponsor, Rolls-Royce plc, is a clear indication of which concepts are feasible for cryogenic cooling systems, along with a toolset that ii advances the companies capability in this research area. This will prove valuable in proposed future projects, most crucially as distributed propulsion technology matures and the need for superconducting components grows. Furthermore, identification of the compressor and turbine as the most critical technologies to develop highlights that Rolls-Royce’s expertise could be used to commercial advantage if high-power cryogenics are ever required.
Keywords: Distributed propulsion; cryogenics; superconductors; systems engineering; all-electric thrust aircraft (AETA); electrical networks